2020
DOI: 10.15366/rimcafd2020.77.006
|View full text |Cite
|
Sign up to set email alerts
|

Relación Entre VFC Post-Ejercicio Y La Carga Interna De Entrenamiento en Triatletas

Abstract: Queremos agradecer a los entrenadores del equipo de triatlón de la Comisión del Deporte del Estado de Sonora por permitirnos llevar a cabo este estudio. We want to thank Mexico´s Sonora State Sports Commission´s triathlon team coaches for allowing us to carry out this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…In contrast, high-intensity exercise is primarily powered by the anaerobic glycolytic metabolic system, which leads to a large increase in blood lactate concentrations during exercise, triggering metabolic reflexes that inhibit parasympathetic activity, and in turn lower HRV. Collectively, these physiological mechanisms create intuitive rationales for the significant associations between running speed and TL HRV found in our analyses ( González-Fimbres et al, 2020 ).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In contrast, high-intensity exercise is primarily powered by the anaerobic glycolytic metabolic system, which leads to a large increase in blood lactate concentrations during exercise, triggering metabolic reflexes that inhibit parasympathetic activity, and in turn lower HRV. Collectively, these physiological mechanisms create intuitive rationales for the significant associations between running speed and TL HRV found in our analyses ( González-Fimbres et al, 2020 ).…”
Section: Discussionmentioning
confidence: 69%
“…Zhao et al have investigated correlations between TL HRV and TRIMP in female soccer athletes; they investigated TL HRV at 60% and 85% maximal speed of the graded maximal test and found moderate correlations between TL HRV and TRIMP ( Zhao et al, 2018 ). Moderate negative correlations between post5 RMSSD and TRIMP were reported by González-Fimbres in the high-intensity interval and low-intensity continuous running of youth triathletes ( González-Fimbres et al, 2020 ). Orellana et al observed moderate correlations between post10 RMSSD and TRIMP by examining 14 healthy men who ran at ventilatory thresholds (VT1 and VT2) and maximal aerobic speed ( Orellana et al, 2019 ).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This parameter is also used in research on emotional control. Furthermore, one of the research publications regarding triathletes [35] The HRV parameters obtained by the respondents from group 2 (subjects 14, 16 and 18 in Table 2) are greater than the adopted norms. This could indicate a light cognitive load.…”
Section: Discussionmentioning
confidence: 88%
“…El LnRMSSD, como era de esperar, desciende después del ejercicio y el SS aumenta inmediatamente en la toma FINAL respecto a la toma BASAL, por la suspensión casi total de la actividad parasimpática y elevación simpática, tal como lo han reportado varios estudios [31][32][33][34]. Se ha descrito dentro de la literatura que esto se pudiera deber a que cuanto mayor es la intensidad relativa del ejercicio, mayor es la carga metabólica (H + , fosfato inorgánico, liberación de epinefrina), que tendrá un efecto sobre la estimulación barorrefleja y metabolorrefleja que estaría relacionado con una baja actividad parasimpática y una alta actividad simpática [10,[35][36][37].…”
Section: Discussionunclassified